Perceptions of health and illness among the Konso people of southwestern Ethiopia: persistence and change - Tebaber Workneh; Guday Emirie; Mirgissa Kaba; Yalemtsehay Mekonnen; Helmut Kloos (BMC, 2018)
Abstract Background Cross-cultural studies indicate that every culture has its own particular explanations for health and illness and its own healing strategies. The Konso people have always practiced indigenous medicine and have multifaceted accounts or multiple dimensions of illness perceptions and health-care beliefs and practices. This paper describes how perceptions of health and illness are instrumental in health and treatment outcomes among the Konso people in southwestern Ethiopia. Results may provide an understanding of the perceptions of health and illness in relation to the local cosmology, religion, and environment. Methods The ethnographic method was employed to generate evidence, complemented by focus group discussions, in-depth interviews, and direct observation. Thematic analysis was employed to categorize and interpret the data. Results Findings indicate that the Konso people's worldview, particularly as it relates to health, illness, and healing systems, is closely linked to their day-to-day lives. Older people believe illnesses are caused by a range of supernatural forces, including the wrath of God or local gods, oritta (spirit possession), and karayitta (ancestral spirits), and they use culturally prescribed treatment. Young and formally educated members of the community attribute causes of diseases to germitta (germs) and factorta (bacteria) and tend to seek treatment mostly in modern health facilities. Conclusion Perceptions of health and illness as well as of healing are part of Konso people's worldview. Local communities comprehend health problems and solutions within their cultural frame of reference, which has changed over the years. The Konso people associate their health situations with socio-cultural and religious factors. The individual's behavior and interactions with the social, natural, and supernatural powers affect the well-being of the whole group. The individual, the family, the clan leaders, and the deceased are intimately linked to one's culturally based health beliefs and are associated by the Konso with health problems and illnesses.